Lung cancer in never smokers in the UK Million Women Study - Pirie, K; Peto, R; Green, J; Reeves, G; Beral, V (Wiley, 2016)
To assess directly the effects of various risk factors on lung cancer incidence among never smokers, large prospective studies are needed. In a cohort of 1.2 million UK women without prior cancer, half (634,039) reported that they had never smoked. Mean age at recruitment was 55 (SD5) years, and during 14 (SD3) years of follow‐up, 0.2% (1,469) of these never smokers developed lung cancer. Cox regression was used to estimate relative risks (RRs) of lung cancer for 34 potential risk factors, of which 31 were nonsignificant (p > 0.05). The remaining three risk factors were associated with a significantly increased incidence of lung cancer in never smokers: non‐white vs. white ethnicity (RR = 2.34, 95% CI 1.55–3.52, p < 0.001), asthma requiring treatment vs. not (RR = 1.32, 1.10–1.58, p = 0.003) and taller stature (height ≥ 165 cm vs. <160 cm: RR = 1.16, 1.03–1.32, p = 0.02). There was little association with other sociodemographic, anthropometric or hormonal factors, or with dietary intakes of meat, fish, fruit, vegetables and fiber. The findings were not materially affected by restricting the analyses to adenocarcinomas, the most common histological type among never smokers.